Dysarthria in pallidal Deep Brain Stimulation in dystonia depends on the posterior location of active electrode contacts: a pilot study. (February 2018) - Pauls, K.A.M.; Bröckelmann, P.J.; Hammesfahr, S.; Becker, J.; Hellerbach, A.; Visser-Vandewalle, V.; Dembek, T.A.; Meister, I.G.; Timmermann, L.
Abstract: Background: Pallidal Deep Brain Stimulation (GPi-DBS) is an efficient treatment for primary dystonia. We investigated stimulation-induced dysarthria, which is the most frequent side-effect of GPi-DBS. Methods: Speech was recorded while reading a standard text, and performing rapid syllable repetitions ON and OFF DBS in ten dystonia patients (6 men; 3 cervical, 4 segmental, 3 generalized, unselected for DBS-related speech impairments). Speech and articulation rate, pauses, and syllable repetition rates were extracted via acoustic analysis. Locations of active stimulation contacts and volumes of tissue activated (VTA) were calculated. Results: The number of pauses increased significantly ON vs. OFF stimulation (Wilcoxon test, p < 0.05). More posteriorly localized active contacts were associated with slower syllable repetition (Pearson correlation, p < 0.05). VTA size did not correlate with any measure of dysarthria. Conclusion: Using quantitative acoustic signal analysis, this study demonstrates that GPi-DBS alters motor aspects of speech. Both inadvertent stimulation of parts of the internal capsule, or interference with GPi function and outflow are possible causes. Understanding causes of GPi-DBS-induced speech changes can improve DBS programming. Highlights: We investigated stimulation-induced dysarthria, the most frequent side-effect of GPi-DBS. GPi-DBS alters motor aspects of speech production. More posteriorly localized active DBS contacts were associated with more speech impairment. Understanding causes of GPi-DBS-induced speech changes can improve DBS programming.